Histone H2A phosphorylation recruits topoisomerase IIα to centromeres to safeguard genomic stability. (26th November 2019) - Zhang, Miao; Liang, Cai; Chen, Qinfu; Yan, Haiyan; Xu, Junfen; Zhao, Hongxia; Yuan, Xueying; Liu, Jingbo; Lin, Shixian; Lu, Weiguo; Wang, Fangwei
Abstract: Chromosome segregation in mitosis requires the removal of catenation between sister chromatids. Timely decatenation of sister DNAs at mitotic centromeres by topoisomerase IIα (TOP2A) is crucial to maintain genomic stability. The chromatin factors that recruit TOP2A to centromeres during mitosis remain unknown. Here, we show that histone H2A Thr‐120 phosphorylation (H2ApT120), a modification generated by the mitotic kinase Bub1, is necessary and sufficient for the centromeric localization of TOP2A. Phosphorylation at residue‐120 enhances histone H2A binding to TOP2A in vitro . The C‐gate and the extreme C‐terminal region are important for H2ApT120‐dependent localization of TOP2A at centromeres. Preventing H2ApT120‐mediated accumulation of TOP2A at mitotic centromeres interferes with sister chromatid disjunction, as evidenced by increased frequency of anaphase ultra‐fine bridges (UFBs) that contain catenated DNA. Tethering TOP2A to centromeres bypasses the requirement for H2ApT120 in suppressing anaphase UFBs. These results demonstrate that H2ApT120 acts as a landmark that recruits TOP2A to mitotic centromeres to decatenate sister DNAs. Our study reveals a fundamental role for histone phosphorylation in resolving centromere DNA entanglements and safeguarding genomic stability during mitosis. Synopsis: Chromosome segregation requires timely decatenation of sister chromatids at mitotic centromeres by topoisomerase IIα (TOP2A). Histone H2A threonine‐120 phosphorylation by Bub1 recruits TOP2A to mitotic centromeres to decatenate sister DNAs, thereby safeguarding genomic stability. Bub1‐mediated histone H2A threonine‐120 phosphorylation (H2ApT120) during mitosis is necessary and sufficient for the centromeric localization of TOP2A. Phosphorylation at Thr120 enhances histone H2A binding to TOP2A in vitro . The C‐gate and the extreme C‐terminal region of TOP2A are important for its H2ApT120‐dependent localization to mitotic centromeres. H2ApT120‐mediated localization of TOP2A at centromeres facilitates the timely decatenation of sister chromatids. Abstract : Bub1‐mediated mitotic phosphorylation of H2A threonine‐120 is necessary and sufficient for topoisomerase IIα (TOP2A) centromeric localization and decatenation of sister chromatids.